Evaluation of delay on unsignalized intersections - Baid, Rodrigo S. (1996)
In this study empirical models of capacity and delay have been developed for two-way STOP controlled intersections. The capacity model states thgat the maximum flow or capacity of the minor street is a function of the total conflicting flow and the basic traffic flow theories regarding capacity was confirmed true. The delay model states that at 100 vph reserved capacity, the average service time tends to remain at a nearly constant level and average service time is a function of total conflicting flow and reserved capacity being fixed. The basic traffic flow theories of delay is also confirmed true in this model. The delay model is in the form of a linear function while the capacity model is in an exponential form. Warrant for signalization or improvement of the intersection has also been developed on some types of intersections.This is a delay based warrant and states that the intersection can is efficient at a combination below the curve of the capacity minus the threshold value of 100vph reserved capacity. In the comparison made otf this established warrant to the MUTCD and the locally used TEC warrant, it was found that the use of either the two existing warrant will overestimate the Philippine situation of unsignalized intersection efficiency. The abovementioned models and the established warrant are preliminary for reason of limited survey sites and data such that the author understands the necessity for further study to come up with a reliable conclusions regarding the characteristics and efficiency of unsignalized intersections in the country.